Analysis of Volatile Flavor Characteristics of Different Types of Air-dried Jerky Based on Electronic Nose Combined with HS-GC-IMS Technology - Yuanxi HAN; Siyuan JIANG; Erhao ZHANG; Zhendong LIU; Bei XUE; Liang LI (Shipin gongye ke-ji)
To investigate the flavor composition and characteristics of air-dried jerkies that are confused and difficult to distinguish with naked eye on the market, electronic nose (E-Nose) combined with headspace-gas chromatography-ion mobility spectrometry (HS-GC-IMS) was used to analyze the flavor profiles and compositions of different jerky types, including air-dried yak, beef, chicken, duck and pork jerkies. Through relative odor activity value (ROAV) and multivariate statistical analysis, the key volatile compounds and characteristic volatile compounds that contributed significantly to the overall flavor of different jerkies and helped distinguish between jerky types were screened. The E-Nose results showed that the overall flavor profiles of different jerkies were similar, although their responsiveness differed. A total of 42 volatile compounds were identified by HS-GC-IMS, including 9 alcohols, 5 ketones, 9 terpenes, 2 acids, 8 esters, 6 aldehydes, 2 pyrazines, and 1 furan. Among them, the highest percentage of relative content of alcohol compounds was 16.04% to 32.41%. The comprehensive analysis revealed that the principal component analysis based on E-nose data achieved good discrimination, and that the flavor profiles differed across different jerky types. The key volatile compounds of various jerkies included (R/S)-linalool, 3-hydroxy-2-butanone, α-pinene, ethyl acetate, isovaleraldehyde, 1-nonyl aldehyde, 1,8-cineole and β-myristate. Among them, isovaleraldehyde and 3-hydroxy-2-butanone-D were key volatile substances and characteristic volatile compounds, whose relative contents were correlated with chicken and yak jerkies, respectively. In conclusion, by analyzing the characteristics of flavour characteristics for different types of air-dried jerkies, which could provide theoretical support for the differentiation of air-dried jerky types.